Pendidikan Islam Masa Pra Kemerdekaan; Telaah Kebijakan Pendidikan Islam Masa Penjajahan - Khusnan Iskandar; Ahmad Syahrul Ansori (Journal of Education and Religious Studies, 2022)
This article conveys about the dynamics of Islamic education in the Pre-Independence era, Islamic boarding school education as native Indonesian education, as well as the development of Indonesian Islamic education during the colonial period, both the Dutch and Japanese colonial periods. The influence of colonialism cannot be denied in the current Islamic education system. This study uses a qualitative method which is a literature review by analyzing related sources. The development of Indonesian education is quite dynamic, greatly influencing various directions of the Indonesian Nation. The importance of exploring the noble values of national identity to improve things that need to be fixed in the field of education. It can be concluded that we are too hegemony with the policies of the colonialists, unfortunately these influences are still embedded today in education in general.